Genetic diversity of microsatellite loci in Leopardus pardalis, Leopardus wiedii and Leopardus tigrinus - Grisolia, A. B. [UNESP] (2007)
The microsatellite loci FCA045, FCA077, FCA008, and FCA096 are highly variable molecular markers which were used to determine the genetic diversity in 148 captive Leopardus sp. The PCR-amplified products of microsatellite loci were characterized in ABI Prism 310 Genetic Analyzer. Allele numbers, heterozygosity, polymorphism information content, exclusive allele number, and shared alleles were calculated. Sixty-five alleles were found and their sizes ranged from 116 to 216 bp in four microsatellite loci. The heterozygosity ranged from 0.36 to 0.81 in Leopardus pardalis, 0.57 to 0.67 in L. tigrinus and 0.80 to 0.92 in L. wiedii. The polymorphism information content was from 0.80 to 0.88 in L. pardalis, 0.76 to 0.88 in L. tigrinus and 0.77 to 0.90 in L. wiedii. The margay (L. wiedii) showed the highest index of polymorphism among the three species in this study. These results imply that microsatellite DNA markers can help in the study of the genetic diversity of Leopardus specimens. ©FUNPEC-RP.